HOW MUCH DOES LOW BIRTH WEIGHT RELATE TO THE AGE OF PREGNANT WOMEN - Dhito Dwi Pramardika; Merty Claudia; Meityn Disye Kasaluhe (Universitas Negeri Gorontalo, 2022)
Low Birth Weight (LBW) in Indonesia is still high. 11 out of 100 mothers who give birth in Indonesia experience children born alive with LBW incidence. These events have an increased risk of morbidity, disability, and even mortality in their lives if serious prevention efforts are not taken. The age of pregnant women is suspected to be one of the causative factors, and the public, even health workers, always say the age of pregnant women is related to the incidence of LBW. But how close is that relationship? The purpose of this study was to find out the relationship between the age of pregnant women and the incidence of LBW. This study uses a retrospective case-control approach with sampling techniques using total sampling. The sample size used a 1:1 ratio of 44 respondents (22 cases and 22 controls) with toddlers 19 months of age as matching in the determination of control samples. Research location at Puskesmas Loa Bakung Samarinda. Data collection uses questionnaires, medical records, and cohorts of pregnant women. The data is analyzed using the chi-square test, contingency coefficient and continued to calculate the odds ratio. The results in the study were that the age of pregnant women was associated with the incidence of low birth weight (0.013 Î±). The level of weak relationship intensity (0.387) and the OR score of 6,500 means the mother's ageâ‰¥ 35 years have a risk of 6,500 times giving birth to a child with LBW compared to mothers aged 20-34. The conclusion of this study requires special attention in pregnant women aged â‰¥ 35 years.